Survival after long-term ART exposure: Findings from an Asian patient population retained in care beyond 5 years on ART - Rimke Bijker (2022)
Background: This study investigated survival in people living with HIV being followed-up from 5 and 10 years after antiretroviral therapy (ART) initiation in a multi-country Asian cohort. Methods: We included patients in follow-up >5 years after ART initiation. Factors associated with mortality beyond 5 and 10 years on ART were analysed using competing risk regression with time-updated variables. Results: Of 13,495 patients retained after 5 years on ART, 279 subsequently died (0.56/100 person-years). Increased mortality was associated with age >50 years (sub-hazard ratio [sHR] 2.24, 95% CI 1.58, 3.15, compared with ≤40 years), HIV exposure through injecting drug use (sHR 2.17, 95% CI 1.32, 3.56), HIV viral load ≥1,000 copies/ml: sHR 1.52, 95% CI 1.05, 2.21, compared with <400), regimen (second-line regimen: sHR 2.11, 95% CI 1.52, 2.94, and third-line regimen: sHR 2.82, 95% CI 2.00, 3.98, compared with first-line regimen), HBV coinfection (sHR 2.23, 95% CI 1.49, 3.33), fasting plasma glucose ≥126 mg/dl (sHR 1.98, 95% CI 1.22, 3.21, compared with <100 mg/dl) and estimated glomerular filtration rate <60 ml/min/1.73 m2 (sHR 2.57, 95% CI 1.56, 4.22). Decreased mortality was associated with transmission through male-to-male sexual contact (sHR 0.44, 95% CI 0.22, 0.88, compared with heterosexual transmission) and higher CD4+ T-cell count (200-349 cells/µl: sHR 0.27, 95% CI 0.20, 0.38, 350-499 cells/µl: sHR 0.10, 95% CI 0.07, 0.16 and ≥500 cells/µl: sHR 0.09, 95% CI 0.06, 0.13, compared with <200 cells/µl). Results after 10 years were similar, but most associations were weaker due to limited power. Conclusions: Next to preventing ART failure, HIV programmes should carefully monitor and treat comorbidities, including hepatitis, kidney disease and diabetes, to optimize survival after long-term ART exposure.